Modelling cyber physical social systems using dynamic time petri nets - Pasandideh, Shabnam (2018)
Performance evaluation models and techniques have been studied broadly in many fields. With the blooming of Cyber-Physical Systems (CPSs), Internet of Things (IoT) and other concepts in distributed systems, usage of a reliable and simple modelling strategy is becoming more important. This paper presents a Petri nets based strategy supporting behavioural modelling as well as performance analysis of Cyber-Physical-Social Systems (CPSSs) covering uncertainty situations when the social factor is also playing an effective role in the performance of these systems. The integration and interaction of system components including computation, physics and social factors as a challenging part of these systems are considered. Petri nets models, augmented with dynamic time dependencies associated with transitions, are applied in a case study, and validated as a promising tool for modelling and analysis of these kind of systems.